A ironia como produção do humor em charges políticas: uma análise da quebra das máximas conversacionais - CARDOSO, Hérika Cristina dos Santos (2019)
The present work has like objective research the irony and humor about of the linguage of politics charges. Understand of the notion of irony like affirmative of thing diferent that if desire to rapport, in what, the issuelet transparent one opposition affirmative for model of the context that ifinvolve the situation. And to show like the humor can be build departing of one pragmatic perspective. More particulary, pursuit to explain the form like the humor is build of the charges departing of the cancel of consequence and of the maxims broke conversation. This work has found on the theory of the consequence of Grice (1982) and, aftermathly, if utilized of the concept of initial of Cooperation and Maxims Conversation of the same author for to do stand to analyses. For such, utilize how corpus of analyses 11 charges politics publish on the internet of differents authors. Like methodology, were point the maxims broke conversation of each charge analysised, and like the cancel of the possible consequence does to arise the humor.